2005
DOI: 10.1143/jjap.44.4784
|View full text |Cite
|
Sign up to set email alerts
|

Sol–Gel-Derived Zn(1-x)MgxO Thin Films Used as Active Channel Layer of Thin-Film Transistors

Abstract: Sol–gel derived n-type Zn(1-x)Mg x O (x=0–0.45) thin films and thin-film transistors (TFTs) with active channel layers made of the films were investigated. The films were prepared at 500°C. The effects of Mg doping on the crystallinity, optical transparency, grain size, and charge-carrier concentration (n) of the films were examined. The Fermi level of the films, as derived from the temperature dependence of n, was ∼0.12 eV below the conduction band. The donor concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…16) A ZnO channel layer that incorporates 20 at% Mg can improve on/off current ratio by five orders of magnitude. However, for films that incorporate 20 at% Mg, the off-current increases as applied gate voltage (V G ) goes from À50 to À80 V. The ionic radius of Zr þ4 (0.8 Å ) is larger than Zn þ2 (0.74 Å ).…”
Section: Introductionmentioning
confidence: 99%
“…16) A ZnO channel layer that incorporates 20 at% Mg can improve on/off current ratio by five orders of magnitude. However, for films that incorporate 20 at% Mg, the off-current increases as applied gate voltage (V G ) goes from À50 to À80 V. The ionic radius of Zr þ4 (0.8 Å ) is larger than Zn þ2 (0.74 Å ).…”
Section: Introductionmentioning
confidence: 99%
“…10,11) ZnO-based semiconductor films have been shown to be suitable for service as TFT active channel layers. [12][13][14][15] Kwon et al 16) indicated that to control the carrier density of the active layer in a ZnO-based TFT is a challenge, because the active layer supplies high carrier density that will be conducting when an applied gate voltage is absent. The ionic radius of Mg 2þ (0.065 nm) is smaller than Zn 2þ (0.074 nm), and thus the solid solubility limit of MgO in ZnO can approach 40 at%.…”
Section: Introductionmentioning
confidence: 99%
“…The TFT exhibited a mobility of 0.2 cm 2 /V s. Cheng et al 17 also fabricated a transparent ZnO TFT using a combination of sol-gel and chemical bath deposition methods. The optimum device had a mobility of 0.67 cm 2 /V s. Lee et al 18 used dip coating to deposit Zn 1Àx Mg x O films. At x = 0.2, the active layer of that TFT showed an on/off current ratio of 10…”
Section: Introductionmentioning
confidence: 99%